THE IMPACT OF ECONOMIC REFORM POLICIES ON IRAQ'S OVERALL BALANCE SHEET - Zena Tariq Ali; Saad Khalaf Mahaws Hamd Al-Jubouri (Scholars Digest Publishing, 2025)
The role of the government in formulating economic reform policies is to achieve macroeconomic balance, which is reflected in economic diversification, increasing non-oil exports, rationalizing government expenditures, and modernizing the investment climate. This study aims to analyze the impact of economic reform policies on Iraq's overall balance from 2000 to 2023 by determining the effect of government consumption, total investment, government expenditure, and net exports. An inductive analysis method was used to test its impact on the overall weight, and the study's results showed a lack of significance. Government consumption affects the overall equilibrium, while total investment, government expenditure, and net exports significantly affect the overall equilibrium. This study provides an analytical vision of the success of Iraq's economic reforms in achieving overall balance. It can help formulate more effective and sustainable economic reform policies suitable for Iraq's economic challenges.
Keywords: Economic reform policies, fiscal policies, monetary policies, macro equilibrium.